1980
DOI: 10.1111/j.1476-5381.1980.tb09767.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucine‐enkephalin and Methionine‐enkephalin Produce Opposing Effects on Plasma Corticosterone Levels in Ether‐stressed Mice

Abstract: The inhibitory effects of intracerebroventricular administration of saline on the plasma corticosterone response to ether stress in mice was reduced by Met‐enkephalin and enhanced by Leu‐enkephalin. When administered simultaneously the effects of the two peptides opposed each other. Met and Leu‐enkephalin may subserve different physiological functions in the response of the hypothalamus‐pituitary‐adrenal system to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Stengaard-Pedersen and L. -1. Larsson, manuscript in preparation) goes along with the observations of a differentiated release of the enkephalins (Corbett et al, 1980) and of a differentiated activity of Leu-and Met-enkephalin in at least one biological system (Gibson et al, 1980). The distribution of Met-and Leuenkephalin-immunoreactive nerve terminals in brain also agrees with the distribution of two types of opiate receptors with different sensitivity to the enkephalins (Goodman et al, 1980).…”
Section: Discussionsupporting
confidence: 61%
“…Stengaard-Pedersen and L. -1. Larsson, manuscript in preparation) goes along with the observations of a differentiated release of the enkephalins (Corbett et al, 1980) and of a differentiated activity of Leu-and Met-enkephalin in at least one biological system (Gibson et al, 1980). The distribution of Met-and Leuenkephalin-immunoreactive nerve terminals in brain also agrees with the distribution of two types of opiate receptors with different sensitivity to the enkephalins (Goodman et al, 1980).…”
Section: Discussionsupporting
confidence: 61%
“…To confirm that this three-session exposure does cause a stress reaction, plasma corticosterone concentration was assessed 10 min after the end of the third ether exposure. A robust elevation in the steroid hormone was observed (32.8 lg/dl compared to 8.3 lg/dl for untreated controls, n = 4 each) as assayed by a commercial EIA immunoassay, indicating that our treatment paradigm also causes a typical stress reaction established for single-exposure procedures [16][17][18][19][20].…”
Section: Ether-induced Tau Phosphorylationmentioning
confidence: 73%
“…Ether‐induced sharp rise in plasma corticosterone concentration attains a peak in about 30 min and reverts to basal levels by about 2 h after ether exposure in rodents [16,17]. Ether anesthesia is thus considered to elicit a typical stress response, and has been employed in numerous neuroendocrinological studies of stress (e.g., [18–20]). Here, we take advantage of ether anesthesia to examine whether and how tau phosphorylation takes place in this peculiar situation of stress without motor activity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our previous study where a high CORT level was found upon chronic isolation [31] , in this study we found low levels of CORT in the blood serum of chronically stressed animals relative to the control. This discrepancy is likely due to the exclusion of ether anesthesia prior to sacrifice [32][33][34] . The current finding of low CORT in isolated animals is similar to the results of other authors showing HPA axis hypoactivity in stress conditions caused by isolation on either young animals or animals subjected to social isolation for shorter periods of time [35,36] .…”
Section: Discussionmentioning
confidence: 99%